We can go [book with audioplayer] - Barkman, Rod (Decodables. Level 2 - red set, 2024)
"There are lots of places to go and things to see. We can travel in lots of different ways too. Let's go! We Can Go is part of Decodables by Jump!, a comprehensive library of decodable leveled readers that follow a sequenced approach to phonics instruction. Young readers will enjoy colorful, photo-packed nonfiction as they follow a prescribed format supported by the science of readers that encourages reading development"--